Volume 6: Nick Newman Symposium on Marine Hydrodynamics; Yoshida and Maeda Special Symposium on Ocean Space Utilization; Specia 2008
DOI: 10.1115/omae2008-57891
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Studies of the Wave Energy Hyberbaric Device for Electricity Production

Abstract: Small scale experiments and numerical simulations have been performed to evaluate a new concept of converter to produce electricity from wave energy. The models, tested in scale 1:10, have been submitted to different regular waves, with height and period representatives of the Brazilian coast, to evaluate the power generation and efficiency. The tests were carried out in a wave basin able to simulate in scale the wave conditions. Software especially written for the simulation of the converter behavior under re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Figure 13 shows the average hydraulic power absorbed by one pumping module as a function of the IMP position reference of the HSS control, for sea states with T av of 6 s and different values of H s from 0.7 to 1 m. The hydraulic power is proportional to the HSS input flow and the pressure p 1 . As the theoretical power per meter of incident wavefront is proportional to the square of the significant wave heights, that is P w ≈ 0.5H 2 s T av , curves with higher plateaus are observed for significant waves heights of 0.9 and 1.0 m. It can be observed that each power curve presents a maximum point of power conversion, which corresponds to the IMP position as calculated by (20). For example, when H s = 0.7 m, the maximum power point is reached at 𝛿 ref = 0 m. Then, the HSS pressure stabilizes at values close to its optimum value of 2 × 10 6 N∕m 2 and the average hydraulic power transferred to the HSS is about 0.08 p.u.…”
Section: Analysis Of the Power Conversionmentioning
confidence: 87%
See 3 more Smart Citations
“…Figure 13 shows the average hydraulic power absorbed by one pumping module as a function of the IMP position reference of the HSS control, for sea states with T av of 6 s and different values of H s from 0.7 to 1 m. The hydraulic power is proportional to the HSS input flow and the pressure p 1 . As the theoretical power per meter of incident wavefront is proportional to the square of the significant wave heights, that is P w ≈ 0.5H 2 s T av , curves with higher plateaus are observed for significant waves heights of 0.9 and 1.0 m. It can be observed that each power curve presents a maximum point of power conversion, which corresponds to the IMP position as calculated by (20). For example, when H s = 0.7 m, the maximum power point is reached at 𝛿 ref = 0 m. Then, the HSS pressure stabilizes at values close to its optimum value of 2 × 10 6 N∕m 2 and the average hydraulic power transferred to the HSS is about 0.08 p.u.…”
Section: Analysis Of the Power Conversionmentioning
confidence: 87%
“…Two stages are defined according to the body motion: (a) the high-pressure stage occurs during the downward motion of the body, when water is injected into the accumulator; (b) the low-pressure stage occurs during the upward motion FIGURE 2 Schematic of the accumulator and variables of the HSS model of the body, when the pump is filled with water. Thus, the PTO force is defined as [20]…”
Section: Pumping Modulesmentioning
confidence: 99%
See 2 more Smart Citations
“…A wave energy hyperbaric converter (WEHC) is a top-mounted pitching point wave energy converter (WEC) device, which mainly consists of three different sub-systems: floater, lever arm and a complex hydraulic power take-off (PTO) system [1,2]. The floater is connected by a lever arm to a hinge in the support platform where the rotational motion of the lever arm is damped by a PTO system to absorb power in operational conditions.…”
Section: Introductionmentioning
confidence: 99%